A new perturb and observe MPPT algorithm based on two steps variable voltage control - Hussain Attia; Suleyman Ulusoy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Based on the fact that the effectiveness of perturb and observe algorithm in a maximum power point tracking maximum power point tracking (MPPT) in a photovoltaic array is a tradeoff between the tracking speed during the transient response and the oscillation around the stable level during the steady state response. To have a high tracking speed, incremental step should be high, but this high incremental step increases the oscillation level around the steady level of MPPT, whereas adopting low incremental step reduces the algorithm response time but improve the response during the steady state condition. This paper presents a new perturb and observe algorithm based on two step variable control for MPPT applications. A two variable incremental step control is proposed to gain the merit of high step for guaranteeing a fast response during tracking process, and also for guaranteeing the merit of low oscillation during the steady state working condition through adopting a low step during steady state response. The effectiveness of the proposal is proved by the analysis of the simulation results via MATLAB/Simulink software, and by the comparison of the simulation results with a conventional perturb and observe MPPT algorithm.